2010
DOI: 10.5539/ijps.v2n1p142
|View full text |Cite
|
Sign up to set email alerts
|

Adjustment of College Freshmen: the Importance of Gender and the Place of Residence

Abstract: This study aims at finding out the effect of gender and place of residence on the adjustment of freshmen in the university. The researcher studied a sample of 117 freshmen in Tafila Technical University. The subjects come from different districts in Jordan. The measurement of college adjustment was applied. This scale consists of 36 items distributed on four dimensions. Means and standard deviations were used to analyze the data. The result s showed that male students are more inclined to adjustment than femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…There is a restricted analysis on assessing the adjustment processes of scholars in universities and not a lot of work is done on student adjustment and connected interventions in African nation [ 18 ]. It is crucial to convey correct attention to the issues involving adjustment among freshmen students [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is a restricted analysis on assessing the adjustment processes of scholars in universities and not a lot of work is done on student adjustment and connected interventions in African nation [ 18 ]. It is crucial to convey correct attention to the issues involving adjustment among freshmen students [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies, including ones in Indonesian context, showed that first-year college students' adjustment could also be explained by their internal factors, such as personality (Ying & Han, 2006;Hirai et al, 2015), self-efficacy (Chemers, Hu, & Garcia, 2001;Irfan & Suprapti, 2014;Majer, 2009;Wijaya, 2012), and gender (Enoch & Rolland, 2006). The contribution of external factors, such as parental factors (Yazedjian, Toews, & Navarro, 2009;Wijaya, 2012) or place of living (Al-Qaisy, 2010;Enoch & Rolland, 2006) to college adjustment were also confirmed. Further research should consider whether to include or to control these variables when measuring the strength of the effect of SNS use on first-year college students' adjustment.…”
Section: Discussionmentioning
confidence: 85%
“…A previous study found that male students tend to adapt to their new role as a university student much better than females. 45 Better adaptative skills may help male students become well-adjusted to their new roles and prevent them from additional stress with that suffered by their female counterparts.…”
Section: Psychological Distress Based On Healthy Lifestyle Behaviorsmentioning
confidence: 99%